Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme

Le deuxième sexe : l'expérience vécue - Beauvoir, Simone de (Gallimard, 1949)
Dans ce second volume, Simone de Beauvoir entreprend " d'étudier avec soin le destin traditionnel de la femme ", c'est à dire de " situer " la femme. " Comment la femme fait-elle l'apprentissage de sa condition, comment l'éprouve-t-elle, dans quel univers se trouve-t-elle enfermée, quelles évasions lui sont permises, voilà ce que je chercherai à décrire. " D'abord sa formation : dans l'enfance, dans l'adolescence, dans l'initiation sexuelle, tout semble disposé, agencé, pour creuser davantage le fossé naturel qui la sépare de l'homme, pour transformer des différences en inégalité, et cette inégalité en infériorité. Ensuite sa situation : Simone de Beauvoir décrit la femme dans le mariage, avec ses prémisses, ses traditions, ses conséquences ; dans la maternité ; dans la prostitution, dans la société ; dans le vieillissement et la vieillesse. Enfin elle envisage les problèmes qui se posent aux femmes qui " héritant d'un lourd passé, s'efforcent de forger un avenir nouveau "
Keywords: 1900-1999; 1940-1949; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; france; histoire et politique; incontournable; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sex3383; thématiques; écriture des femmes*

Le deuxième sexe : les faits et les mythes - Beauvoir, Simone de (Idées, 1949)
«Nous commencerons par discuter les points de vue pris sur la femme par la biologie, la psychanalyse, le matérialisme historique. Nous essaierons de montrer ensuite positivement comment la «réalité féminine» s'est constituée, pourquoi la femme a été définie comme l'Autre et quelles en ont été les conséquences du point de vue des hommes. Alors nous décrirons du point de vue des femmes le monde tel qu'il leur est proposé ; et nous pourrons comprendre à quelles difficultés elles se heurtent au moment où, essayant de s'évader de la sphère qui leur a été jusqu'à présent assignée, elles prétendent participer au mitsein humain». Simone de Beauvoir.
Keywords: 1900-1999; 1940-1949; cours; discipline; europe; fem1000; france; har4600; histoire et politique; incontournable; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sex3383; thématiques; écriture des femmes*